2004
DOI: 10.1093/jncimonographs/lgh027
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Report on the Occurrence, Assessment, and Treatment of Fatigue in Cancer Patients

Abstract: To determine the occurrence of cancer-related fatigue, the methods used to assess it, and the efficacy of the available treatments, we performed literature searches that identified English-language publications on these topics. Twenty-seven studies were identified in which the quantitative estimation of the occurrence of cancer-related fatigue was an end point. Fifty-six were judged to be relevant to the assessment of fatigue, and 10 randomized controlled clinical trials of treatments of cancer-related fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
250
0
13

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(266 citation statements)
references
References 94 publications
1
250
0
13
Order By: Relevance
“…When fatigue prevalence (26.8%) and intensity (mean=5.8; SD=1.3; median=5.4) in this research were compared to studies involving other cancer patients, it was noted that fatigue was less frequent than in studies on patients in palliative care and receiving adjuvant chemotherapy or radiotherapy (1)(2) , and higher than some cancer survivors' experience, who reported 26% (8) . A slightly higher prevalence of fatigue (33%), using the same cut-off score as this study, was observed among colorrectal cancer patients in the United Kingdom (22) .…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…When fatigue prevalence (26.8%) and intensity (mean=5.8; SD=1.3; median=5.4) in this research were compared to studies involving other cancer patients, it was noted that fatigue was less frequent than in studies on patients in palliative care and receiving adjuvant chemotherapy or radiotherapy (1)(2) , and higher than some cancer survivors' experience, who reported 26% (8) . A slightly higher prevalence of fatigue (33%), using the same cut-off score as this study, was observed among colorrectal cancer patients in the United Kingdom (22) .…”
mentioning
confidence: 60%
“…In a systematic review that included 27 studies, the prevalence ranged from 4% to 91%, depending on the cancer population and assessment instruments (1) .…”
mentioning
confidence: 99%
“…Of 30 patients who took at least one dose of PG, 24 (80%) were evaluable. The patients who were not evaluable had disease progression (3), did not comply with the study protocol (2), or were lost to follow-up (1).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, behavioral side effects of cancer treatment have become a focus of research and clinical attention. The most common and distressing side effect of cancer treatment is fatigue (Lawrence et al, 2004). Fatigue occurs across different types of cancer and cancer treatments and may persist for months or years after successful treatment completion.…”
Section: Introductionmentioning
confidence: 99%